Internacjonalizacja : w kręgu nowej terminologii dwudziestowiecznej debaty ideologicznej i naukowej - Skarzyński, Ryszard (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
There are many specific concepts used in social sciences to describe social phenomena. In this text, the subject of research is internationalization, one of the new terms in the twentieth century, similarly to fascism, communism, authoritarianism, totalitarianism, the political, geopolitics, but also international relations and polyarchy. The article presents the meaning of the concept of internationalization, its genesis and relationships with specific social phenomena to which it should be applied during analysis.
Keywords: internationalization; International Relations; political science; nation state; globalization; polyarchy